Vision in white - Roberts, Nora (Roberts, Nora. Bride quartet, 2009)
The women at Vows, an event planning company in Connecticut, create memorable weddings. Mackensie's photos, Laurel's cakes, Emma's flowers, and Parker's organizational skills combine for a flourishing business. English teacher Carter Maguire serves as a needed distraction from the wedding woes for Mackensie, who has no intention of ruining their relationship by getting married. But as the women of Vows work to nab a huge event, Mackensie may change her mind.